Experiences of Acculturation: Chinese Student Sojourners at the University of Macerata in Italy - Burn, Sarah (My University, 2017)
There has, and continues to be, a dramatic increase worldwide in the number of students traveling abroad for study purposes in higher education. OECD statistical reports show that students from Asia, particularly those from China, constitute the largest incoming group of international students at most universities around the world. Chinese students studying Italian at Chengdu Institute, Sichuan International Studies University (CISISU) came for one full academic year, August 2015 – July 2016, to live and study abroad at the University of Macerata (UNIMC) in Central Italy. The aim of this research is to discover and understand the students’ psychological and sociocultural experiences of acculturative adjustment to changes in academic and daily life during their cross-cultural exchange. This short-term longitudinal study uses Ward et al.’s affective, behavioural, and cognitive (ABC) model of acculturation as a conceptual theoretical framework to analyze the holistic view of the students’ cross-cultural transition. Following the ABC theoretical model, in-depth qualitative research looks into understanding the students’ affective feelings of stress and coping, behavioural experiences of cultural learning, and cognitive thoughts of sociocultural identification between their home society in China, and the host society in Italy. Analytical results from the qualitative semi-structured interviews determined that despite challenges in cultural difference, the Chinese student sojourns experienced a positive exchange that will benefit them for the future. Balancing a bicultural identity, learning the language, dietary acculturation, social support, independence, and the lack of convenient services in the smaller and slower paced sociocultural environment of Macerata are all important factors that affected the students’ sojourn.
Keywords: Chinese exchange students; UNIMC; higher education; cross-cultural transition; acculturation; ABC framework of acculturation; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|